Impact of the microstructure model on coupled simulation of drying and accelerated carbonation. (February 2018) - Georget, Fabien; Prévost, Jean H.; Huet, Bruno
Abstract: During carbonation, the microstructure of a cement paste is strongly modified, which induces a dynamic feedback loop impacting the global advancement of the reaction. In this study, we investigate the effect of the microstructure model on simulations of accelerated carbonation of cement pastes. A variable-porosity reactive transport model with a new microstructure model is used. To match the chemical layers created by the carbonation front, we use a layered microstructure model. We demonstrate that qualitative prediction for a large range of conditions and formulations can only be obtained if the macroscopic parameters of the carbonated layer can be modelled accurately. In particular, the saturation dependent parameters, such as the capillary pressure or the relative diffusion coefficients, control the rate of advancement of the reaction front since a high saturation inhibits the carbon dioxide diffusion.